Analysing smoking cessation approaches towards identifying potential anti-smoking strategy for adult smokers in Kuantan, Pahang, Malaysia - Mohamad Helmy Jaafar (Kulliyyah of Nursing, International Islamic University Malaysia, 2021)
Due to the rapid growth of technology, most people in the community have at least an idea that smoking harm smokers and its surrounding. Despite the fact that various ways have been devised to assist smokers in quitting smoking, smoking addiction still remain to be an issue. Therefore, this research is conducted to analyse the available smoking cessation strategies to develop the potential anti-smoking strategy for adult smokers in Kuantan Pahang, Malaysia. This research is divided into 3 phases thas and Phase 3: to identify one potential approach for anti-smoking strategy based on the outcome of Phase 1 and 2. In Phase 1, the current anti-smoking campaign was judged to be ineffective. New campaign ideas and strategies must be implemented. The community has a high level of anti-smoking knowledge. During this phase, it was discovered that smokers sincerely want to quit smoking, but the system and facilities need to be improved. Systematic search of Cinahl, Proquest and Scopus from year 2007 until 2017 using identified keyword and retrospective data analyses at anti-smoking clinics from period of June 2015 – June 2017 were conducted in Phase 2. This phase found that internet intervention is the best method for smoking cessation worldwide and smokers are advised to stop smoking and seek health professional advice. Findings from Phase 1 and 2 had been used to generate findings for Phase 3. As a result, internet intervention has been chosen to be one of the potential approaches in Phase 3. International website searches were conducted by entering the identified keywords into Google.com. The international websites of Smokefree.gov and NY SmokeFree can be claimed as the most effective designs with extensive coverage on key component of smoking cessation treatment as described in national treatment guidelines. This study managed to adapt the Standardized Checklist to be use in assessing the local smoking cessation website in term of content. Then a cross-sectional study using a mix method was conducted among smokers in Kuantan, Pahang to assess the local website on smoking cessation in two phases: Phase I is the selection of a website by a content expert, and phase II is the review of a selected local website using Standardized Checklist by local respondents. The website JomQuit.com was identified as comprehensive anti-smoking website in Malaysia. Malaysian online smoking cessation websites need to improve their content as well as increase their advertising and promotion across the country. Regular website assessments must be performed on a regular basis to ensure that the information on the website is applicable to local communities and for content improvement purposes. This study benefits the community by presenting a comprehensive anti-smoking website through the use of a standardized checklist.